Cardiac myosin‐binding protein C in the diagnosis and risk stratification of acute heart failure. (5th February 2021) - Kozhuharov, Nikola; Wussler, Desiree; Kaier, Thomas; Strebel, Ivo; Shrestha, Samyut; Flores, Dayana; Nowak, Albina; Sabti, Zaid; Nestelberger, Thomas; Zimmermann, Tobias; Walter, Joan; Belkin, Maria; et al.
Abstract : Aims: Cardiac myosin‐binding protein C (cMyC) seems to be even more sensitive in the quantification of cardiomyocyte injury vs. high‐sensitivity cardiac troponin, and may therefore have diagnostic and prognostic utility. Methods and results: In a prospective multicentre diagnostic study, cMyC, high‐sensitivity cardiac troponin T (hs‐cTnT), and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) plasma concentrations were measured in blinded fashion in patients presenting to the emergency department with acute dyspnoea. Two independent cardiologists centrally adjudicated the final diagnosis. Diagnostic accuracy for acute heart failure (AHF) was quantified by the area under the receiver operating characteristic curve (AUC). All‐cause mortality within 360 days was the prognostic endpoint. Among 1083 patients eligible for diagnostic analysis, 51% had AHF. cMyC concentrations at presentation were higher among AHF patients vs. patients with other final diagnoses [72 (interquartile range, IQR 39–156) vs. 22 ng/L (IQR 12–42), P  < 0.001)]. cMyC's AUC was high [0.81, 95% confidence interval (CI) 0.78–0.83], higher than hs‐cTnT's (0.79, 95% CI 0.76–0.82, P =  0.081) and lower than NT‐proBNP's (0.91, 95% CI 0.89–0.93, P  < 0.001). Among 794 AHF patients eligible for prognostic analysis, 28% died within 360 days; cMyC plasma concentrations above the median indicated increased risk of death (hazard ratio 2.19, 95% CI 1.66–2.89; P  < 0.001). cMyC's prognostic accuracy was comparable with NT‐proBNP's and hs‐cTnT's. cMyC did not independently predict all‐cause mortality when used in validated multivariable regression models. In novel multivariable regression models including medication, age, left ventricular ejection fraction, and discharge creatinine, cMyC remained an independent predictor of death and had no interactions with medical therapies at discharge. Conclusion: Cardiac myosin‐binding protein C may aid physicians in the rapid triage of patients with suspected AHF.